The educational performance of East Coast Bumiputra students / Zamri Mohd Noor - Mohd Noor, Zamri (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
This study of the academic performance of bumiputra students on the East Coast was undertaken in order to examine aspects which can help in promoting academic excellence among East Coast bumiputra students. The socio-economic aspect was adopted as the basis of the study, with emphasis on factors such as environment, family income, and motivation or determination to succeed.